Textbook Outcomes Among Medicare Patients Undergoing Hepatopancreatic Surgery - Merath, Katiuscha; Chen, Qinyu; Bagante, Fabio; Beal, Eliza; Akgul, Ozgur; Dillhoff, Mary; Cloyd, Jordan M; Pawlik, Timothy M (Annals of surgery, 2020)
To define and test "Textbook Outcome" (TO)-a composite measure for healthcare quality-among Medicare patients undergoing hepatopancreatic resections. Hospital variation in TO and Medicare payments were analyzed. Composite measures of quality may be superior to individual measures for the analysis of hospital performance. The Medicare Provider Analysis and Review (MEDPAR) Inpatient Files were reviewed to identify Medicare patients who underwent pancreatic and liver procedures between 2013 and 2015. TO was defined as: no postoperative surgical complications, no prolonged length of hospital stay, no readmission ≤ 90 days after discharge, and no postoperative mortality ≤ 90 days after surgery. Medicare payments were compared among patients who achieved TO versus patients who did not. Multivariable logistic regression was used to investigate patient factors associated with TO. A nomogram to predict probability of TO was developed and validated. TO was achieved in 44% (n = 5919) of 13,467 patients undergoing hepatopancreatic surgery. Adjusted TO rates at the hospital level varied from 11.1% to 69.6% for pancreatic procedures and from 16.6% to 78.7% for liver procedures. Prolonged length of hospital stay represented the major obstacle to achieve TO. Average Medicare payments were substantially higher among patients who did not have a TO. Factors associated with TO on multivariable analysis were age, sex, Charlson comorbidity score, previous hospital admissions, procedure type, and surgical approach (all P > 0.05). Less than one-half of Medicare patients achieved a TO following hepatopancreatic procedures with a wide variation in the rates of TO among hospitals. There was a discrepancy in Medicare payments for patients who achieved a TO versus patients who did not. TO could be useful for the public reporting of patient level hospital performance and hospital variation.